Potential Protective Effect of combined Nebivolol and Candesartan against Cisplatin-induced Nephrotoxicity in Albino Rats - Omer, Jamal Jamil Abdullah (University of Science and Technology, Sana’a, 2026)
This study aimed to investigate the potential protective effect of combined nebivolol and candesartan, separately and in combination, against cisplatin-induced nephrotoxicity in male albino rats. Thirty-five rats weighing 180 ± 30 g were randomly assigned into five groups: control (saline), cisplatin-alone (6 mg/kg i.p., day 24), cisplatin with nebivolol (10 mg/kg p.o. daily), cisplatin with candesartan (8 mg/kg p.o. daily), and cisplatin with combined nebivolol and candesartan. All oral treatments were administered daily for 28 days, with cisplatin given as a single intraperitoneal dose on day 24 to induce nephrotoxicity. Renal function markers, inflammatory cytokines (IL-6, TNF-α), oxidative stress parameters (MDA, GSH, SOD), electrolyte levels (Na⁺ and K⁺), and histopathological changes were assessed. Cisplatin administration resulted in significant renal impairment, characterized by elevated serum creatinine, urea, and blood urea nitrogen; increased pro-inflammatory cytokines, oxidative stress, electrolyte imbalances, and marked histological kidney damage. Treatment with nebivolol or candesartan separately significantly ameliorated these biochemical, inflammatory, and oxidative alterations, as well as improved renal histology. Notably, the combination therapy of nebivolol and candesartan provided superior nephroprotection, restoring most parameters close to normal levels and showing better benefits in reducing cisplatin-induced renal injury. These results suggest that nebivolol and candesartan, each alone and especially in combination, effectively protect against cisplatin-induced nephrotoxicity by targeting oxidative stress, inflammation, and renal dysfunction. Their combined use may represent a promising therapeutic strategy to mitigate kidney damage in patients suffering from hypertension.
Keywords: Nebivolol; Candesartan; Cisplatin; Nephrotoxicity; Pharmacology; Sana'a